Finding a needle in a haystack: whole genome sequencing and mutation discovery in murine models - Rampal, Raajit K. (American Society for Clinical Investigation, 2011)
Acute promyelocytic leukemia (APL) is a malignancy of the bone marrow, in which there is a deficiency of myeloid cells and an excess of immature cells called promyelocytes. APL is most commonly caused by a translocation (15:17) and expression of the promyelocytic leukemia and the retinoic receptor α (PML-RARA) fusion product; however, the events that cooperate with PML-RARA in APL pathogenesis are not well understood. In this issue of the JCI, Wartman and colleagues use an innovative approach to find other relevant mutations in APL. They performed whole genome sequencing and copy number analysis of a well-characterized APL mouse model to uncover somatic mutations in Jak1 and lysine (K)-specific demethylase 6A (Kdm6a, also known as Utx) in mice with APL and validated the ability of Jak1 mutations to cooperate with PML-RARA in APL. The findings implicate the JAK/STAT pathway in the pathogenesis of APL and illustrate the power of whole genome sequencing to identify novel disease alleles in murine models of disease.